Inovasi Gamifikasi Fiqh Ibadah sebagai Media Sarana Penguatan Spiritualitas Peserta Didik - Jaziela Huwaida; Fiftha Oktavianiska Nurhiday (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
This community service research aims to improve students’ understanding of fiqh al-‘ibadah through the implementation of the MARHABA (Media Rukun dan Hukum Ibadah Berbasis Arena) learning media, which was developed in the form of an educational Monopoly-based game. The program was conducted at SMPN 1 Siman and involved 32 students as participants in a three-day  Ramadhan Camp program. The method employed in this study was based on the ADDIE model, which consists of the stages of analysis, design, development, and implementation. The MARHABA media integrates fiqh al-‘ibadah materials through questions, challenges, and guided practice of  worship movements carried out collaboratively in groups. The results of the program indicate that the use of MARHABA successfully created a more interactive and enjoyable learning environment,  increased students’ engagement, and helped them better understand and practice the pillars and movements of worship. Therefore, MARHABA can serve as an innovative alternative learning media for Islamic Religious Education